Effects of Baroreflex Activation Therapy on Ambulatory Blood Pressure in Patients With Resistant Hypertension. Issue 4 (April 2016) - Wallbach, Manuel; Lehnig, Luca-Yves; Schroer, Charlotte; Lüders, Stephan; Böhning, Enrico; Müller, Gerhard A.; Wachter, Rolf; Koziolek, Michael J.
Abstract : Baroreflex activation therapy (BAT) has been demonstrated to decrease office blood pressure (BP) in the randomized, double-blind Rheos trial. There are limited data on 24-hour BP changes measured by ambulatory BP measurements (ABPMs) using the first generation rheos BAT system suggesting a significant reduction but there are no information about the effect of the currently used, unilateral BAT neo device on ABPM. Patients treated with the BAT neo device for uncontrolled resistant hypertension were prospectively included into this study. ABPM was performed before BAT implantation and 6 months after initiation of BAT. A total of 51 patients were included into this study, 7 dropped out from analysis because of missing or insufficient follow-up. After 6 months, 24-hour ambulatory systolic (from 148±17 mm Hg to 140±23 mm Hg, P <0.01), diastolic (from 82±13 mm Hg to 77±15 mm Hg, P <0.01), day- and night-time systolic and diastolic BP (all P ⩽0.01) significantly decreased while the number of prescribed antihypertensive classes could be reduced from 6.5±1.5 to 6.0±1.8 ( P =0.03). Heart rate and pulse pressure remained unchanged. BAT was equally effective in reducing ambulatory BP in all subgroups of patients. This is the first study demonstrating a significant BP reduction in ABPM in patients undergoing chronically stimulation of the carotid sinus using the BAT neo device. About that BAT-reduced office BP and improved relevant aspects of ABPM, BAT might be considered as a new therapeutic option to reduce cardiovascular risk in patients with resistant hypertension. Randomized controlled trials are needed to evaluate BAT effects on ABPM in patients with resistant hypertension accurately. Abstract : Supplemental Digital Content is available in the text.